Pro-inflammatory Profiles of Indonesian Adult Men with Central Obesity: A Preliminary Study on TNF-alpha, sTNFR-2 and IL-1beta - Cynthia Retna Sartika; Andi Wijaya; Suryani As'ad (The Prodia Education and Research Institute (PERI), 2010)
BACKGROUND: Central obesity is closely associated with chronic inflammation, characterized by abnormal cytokine production such as IL-1β, tumor necrosis factor-α (TNF-α) and tumor necrosis factor receptor-2 (TNFR-2). Central obesity and chronic inflammation form a complex link with insulin resistance, leading to the development of type-2 diabetes mellitus (T2DM) and cardiovascular disease (CVD). Knowing the coinciding occurrence of chronic inflammation and central obesity, this study aimed to examine pro-inflammatory cytokine profiles of Indonesian adult men with central obesity.METHODS: This cross-sectional study recruited 80 apparently healthy Indonesian adult men, aged 23-53 years with waist circumference of 64-125 cm. This study was done in Jakarta. Measurements included clinical parameters like systolic blood pressure (SBP), diastolic blood pressure (DBP), fasting blood glucose (FBG), aspartate amino transferase (AST), alanine amino transferase (ALT), creatinine, high sensitivity C-reactive protein (hsCRP), anthropometric parameters, namely weight, height and waist circumference; and pro-inflammatory cytokines TNF-α, soluble TNFR-2 (sTNFR-2) and IL-1β.RESULTS: Basic characteristics of the subjects showed linear increase in values of SBP, DBP and the serum concentrations of AST, ALT, FBG, GFR, hsCRP (p<0.005, respectively) with the degree of obesity. sTNFR-2 and IL-1 β positively correlated with hsCRP (r=0.277, p=0.013 and r= 0.257, p=0.022, respectively), WC (r=0.380, p=0.001 and r=0.400, p<0.001, respectively) and body mass index (BMI) (r=0.364, p=0.001 and r=0.399, p<0.001, respectively). Moreover, TNF-α did not show correlations with hsCRP, WC and BMI.CONCLUSION: There was a linear increase in the serum concentrations of sTNFR-2 and IL-1β in subjects with central obesity. Both pro-inflammatory markers, correlated with hsCRP, WC and BMI, but TNF-α did not. sTNFR-2 and IL-1β were, therefore, considered as valid biomarkers to indicate chronic inflammation in Indonesian adult men with central obesity.KEYWORDS: central obesity, TNF-α, soluble TNFR-2 (sTNFR-2), IL-1β